Patients’ risk for pressure injury in intensive care unit - Campos, Michelle Mayumi Yoshimura de; Souza, Mariana Fernandes Cremasco de; Whitaker, Iveth Yamaguchi (Revista Cuidarte, 2021)
Introduction: Limited sensory perception, immobility, sedation, mechanical ventilation, tissue hypoperfusion, edema and moisture are considered predisposing factors for the development of pressure ulcers in critically ill patients. Objective: To characterize pressure ulcers in critically ill patients, determine the association with demographic variables, stay in hospital and clinical conditions, and identify risk factors for the development of pressure ulcers. Materials and Methods: A cross-sectional was conducted with a sample of patients aged 18 years and older who had no pressure ulcers on admission and had been hospitalized > 24 hours in the Intensive Care Unit. The association of pressure ulcers with each of the variables was assessed using the Mann-Whitney U test, chi-squared test, likelihood ratio, and Fisher’s exact test. Risk factors were identified by multiple logistic regression. Results: Among 324 patients, 46 patients (14.2%) developed pressure ulcers most frequently in sacral and calcaneal regions. Risk factors for pressure ulcers development were age, length of hospital stay and hospital stay before admission to the Intensive Care Unit. Discussion: Such high incidence, location and stage of the identified pressure ulcers expose the vulnerability of intensive care unit patients to this type of injury. Risk factors for pressure ulcers development include aspects related to the patient, hospitalization and disease severity, and their combination should be assessed as part of the daily assessment of the critically ill patient. Conclusions: The occurrence of pressure ulcers in critically ill patients is a multifactorial phenomenon, for which the recognition of risk factors can contribute to the early rapid adoption of measures for their prevention. How to cite this article: Campos, Michelle Mayumi Yoshimura de; Souza, Mariana Fernandes Cremasco de; Whitaker, Iveth Yamaguchi. Risco para lesão por pressão em pacientes de unidade de terapia intensiva. Revista Cuidarte. 2021;12(2):e1196. http://dx.doi.org/10.15649/cuidarte.1196